SURVEI KEPUASAN MASYARAKAT TERHADAP PELAYANAN PUBLIK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KLATEN (PELAYANAN PEMBUATAN E-KTP) - Kamila, Nelly Rifda; Setiyono, Budi; Herawati, Nunik (Journal of Politic and Government Studies, 2018)
This study aims to determine the level of public satisfaction of public services in the Department of Population and Civil Registry of Klaten Regency in serving the making of e-ID card through IKM Conversion Value based on the Regulation of the Minister of Administrative Reform and Bureaucratic Reform No. 14 of 2017 About Guidelines for Arrangement of Public Satisfaction Survey Organizer Unit Public ServiceThis research uses descriptive research type with quantitative approach. The sampling technique used in this research is the non-probability sampling technique by using the result data from the questionnaire, observation, documentation, and unstructured interview.The result of the research shows that the value of Public Satisfaction Index/ Indeks Kepuasan Masyarakat (IKM) of public service on the service of making e-ID card in the Department of Population and Civil Registry of Klaten Regency is 2.91 with IKM conversion rate of 72.75. This result indicates that the level of public satisfaction on the service of making e-ID card in the Department of Population and Civil Registry of Klaten Regency is in the category of less satisfied. The calculation results of the 9 elements of the Satisfaction Index are presented as follows: (1) The requirement has an IKM conversion value of 72.75 with less satisfied category. (2) The procedure has an IKM conversion value of 62 under the category of not satisfied. (3) The service time has an IKM conversion value of 72.75 with less satisfied category. (4) Cost/tariff has an IKM conversion value of 89 with a very satisfied category. (5) Service products have an IKM conversion value. (6) The implementing competence has an IKM conversion value of 73.5 with less satisfied category. (7) Implementing Behavior has an IKM conversion value of 65.75 with less satisfied category. 8) Facilities and infrastructure have an IKM value of 60 with the category of not satisfied. (9) Complaint handling, suggestions and inputs have an IKM conversion value of 51.5 with the category of not satisfied. Community satisfaction is related to the level of one's feelings after comparing perceived performance/result with expectations. If people are not satisfied, this indicates that the performance of the public organizers is not good. To achieve progress of better services, they must realize the importance of increasing work productivity. On another word, the performance of the Department of Population and Civil Registry of Klaten Regency needs to be improved.